1998
DOI: 10.1254/jjp.78.169
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Cytokines for Augmentation of the Antigen-Specific Antibody Responses by Ascorbate in Cultured Murine T-Cell-Depleted Splenocytes

Abstract: To gain a better understanding of the possible mechanisms by which a stable form of ascorbate, ascorbic acid 2-glucoside (AA-2G), as an ascorbate source, augments antibody responses, we examined whether AA-2G enhances the anti-sheep-red-blood-cell (SRBC) plaque-forming cell (PFC) responses elicited with distinct interleukins that provide signals for B-cell proliferation and differentiation in cultured murine T-cell-depleted splenocytes. The anti-SRBC PFC responses were markedly reduced by T-cell depletion; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The level of intracellular AA-2G was undetectable (<17 ng/10 6 cells) at 2 and 4 days after addition (our unpublished data), suggesting that AA-2G is not efficiently transported into the cells. The time course for depletion of intracellular AA is similar to the time courses reported for murine T-cell-depleted splenocytes and human tonsilar B cells in culture [2,27]. Since ␣-glucosidase activity in the medium supplemented with 10% fetal bovine serum is very low for hydrolysis of AA-2G [22], the conversion of AA-2G to AA may be catalyzed by cellular ␣-glucosidase of B lymphocytes.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The level of intracellular AA-2G was undetectable (<17 ng/10 6 cells) at 2 and 4 days after addition (our unpublished data), suggesting that AA-2G is not efficiently transported into the cells. The time course for depletion of intracellular AA is similar to the time courses reported for murine T-cell-depleted splenocytes and human tonsilar B cells in culture [2,27]. Since ␣-glucosidase activity in the medium supplemented with 10% fetal bovine serum is very low for hydrolysis of AA-2G [22], the conversion of AA-2G to AA may be catalyzed by cellular ␣-glucosidase of B lymphocytes.…”
Section: Discussionsupporting
confidence: 75%
“…The initial intracellular concentration of AA is maintained by exogenous AA added to cultures repeatedly at 12-h intervals but not by single addition of AA because of its instability in the culture medium [2]. Single addition of AA-2G, however, is sufficient to restore and maintain the initial intracellular levels of AA for several days as shown in this study and other studies [27,34]. Thus, AA-2G might be a useful tool for investing the physiological role of AA in long culture systems in vitro.…”
Section: Discussionmentioning
confidence: 64%
“…Ascorbic acid enhances the human immune response that enhances the Con A-induced proliferation of PBLs [10], chemotaxis of neutrophils [11], and phagocytosis of mononuclear leukocytes [12]. It has been reported that ascorbic acid upregulates the IgM antibody responses in a cytokine-dependent manner in spleenocytes [13]. The in vitro function of endotoxic shock-induced macrophages and lymphocytes was modulated by ascorbic acid [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have stated that T‐lymphocytes presented CD3 antigen on cell surface membranes are involved in cell‐mediated immunity in cellular immunomodulatory system, and B cells are primarily mediated in humoral immunity (Krop et al,; Mitsuzumi et al,; Lu et al,). Hence, we also examined the cell markers from PBMC of leukemic mice after oral treatment of safrole and our results indicated that the percentages of CD3 (T cells), CD19 (B cells) and Mac‐3 (macrophages) were significantly increased in safrole‐treated leukemic mice, but that the population of CD11b (monocytes) were not significantly affected in leukemic mice after safrole exposure (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…and Table ). It is reported that nonactivated B cells are shown CD19 marker and their differentiation modulate by the interaction of various types of cytokines secreted from macrophages or T cells (Mitsuzumi et al,). Our results showed that safrole could increase B cells (elevated the population of CD19), and the augmenting effect of safrole is carried out through the antibody responses resulted from expansion and differentiation of mainly monocytes and macrophages.…”
Section: Discussionmentioning
confidence: 99%